Clinical efficacy of low-temperature radiofrequency ablation of pharyngolaryngeal cyst in 84 Chinese infants. Issue 44 (November 2017) - Wang, Zhinan; Zhang, Yamin; Ye, Yuhua; Yao, Wei; Xu, Zhongqiang; Xia, Zhongfang; Wang, Shufen; Zhou, Chengyong
Abstract : Abstract: The aim of the study is to investigate the advantages and disadvantages of low-temperature radiofrequency ablation of pharyngolaryngeal cyst. The study population was composed of 84 children diagnosed with pharyngolaryngeal cyst who underwent surgical treatment at the Department of Otolaryngology, Wuhan Children's Hospital, Wuhan, China, between January 1984 and December 2013. All patients were operated using a self-retaining laryngoscope and were divided into 3 groups: traditional cystectomy group (N = 9), dynamic cutting system group (N = 18), and low-temperature radiofrequency ablation group (N = 57). Clinical outcomes were analyzed to assess the efficacy of low-temperature radiofrequency ablation in treatment of pharyngolaryngeal cyst. Compared with traditional cystectomy group or dynamic cutting system group, operation time was shorter, bleeding was less and one-year recurrence rate was much lower in low-temperature radiofrequency ablation group. However, operation time and bleeding was not statistically different between traditional cystectomy and dynamic cutting system group. Low-temperature radiofrequency ablation may be an effective substitute for treating pharyngolaryngeal cyst.